The Classification of Knowledge According to Imam Al-Ghazali - Imron Agung Khoirudin; Muslimah Muslimah (Tasfiyah: Jurnal Pemikiran Islam, 2021)
This journal article aims to explain the relationship between religious science and the classification of science and technology. In the thought of Imam Al-Ghazali, who has a work entitled Ihya Ulumuddin, explained that science cannot be separated from religion, because in essence religion is a unity of science. In other words, religion and science both originate from the creator of Allah's universe. This research uses the descriptive qualitative literature method by relying on theoretical data and documentation in the library. Data collection in this study was obtained by reviewing related literature, with a content analysis approach. The findings of this study explain that the science of religion has an important role in the classification of science, namely as a foundation in building an order of thought, and besides that the science of religion as shari'ah functions as a barometer of whether or not the science is implemented. in human life.